البنية الايقاعية في قصيدة ثورة الشرفاء للشاعر مفدي زكرياء - زين، التجاني, موساوي، محمد; بلقاسمي، عبد القادر (University of El-oued, 2022)
يهدف هذا البحث إلى دراسة البنية الإيقاعية في قصيدة ثورة الشرفاء للشاعر الجزائري مفدي زكريا ، وقد تم فيه التركيز على دراسة أبرز المظاهر المكوّنة للإيقاع على مستواه الداخلي ( التكرار ، نوع الأصوات ، الجناس ، الطباق ، التصريع ) و الخارجي (الوزن والقافية ). This research aims to study the rhythmic structure in the poem Revolution Al-Shurafa by the Algerian poet Moufdi Zakaria, in which the focus has been on studying the most prominent aspects that make up the rhythm on the internal level (repetition, type of sounds, alliteration, counterpoint, inflection) and external (weight and rhyme).
Keywords: البنية – الايقاع - الوزن; structure - rhythm - weight